DAMPAK KONVERGENSI IFRS DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MODERASI - Zuhair, Muhammad Sayyid; Nurdiniah, Dade (Economic Faculty, Attahiriyah Islamic University, 2018)
This study aims to examine the effect of convergence of International Financial Reporting Standard (IFRS), leverage, interaction of convergence IFRS with sales growth and leverage interaction with sales growth on earnings management action on company LQ45 period 2009-2014. Sample selection using purposive sampling method. The sample of this research is 90 companies. The test results show that: 1) the convergence of IFRS as measured by the dummy variable has no effect on the profit management action; 2) the leverage measured by the leverage ratio positively affects the profit management action; 3) the interaction of sales growth as a moderating variable measured by sales growth instead The moderating variable between the convergence of IFRS to the action of earnings management, 4) the interaction of sales growth as a moderating variable can strengthen the leverage effect on earnings management actionshowed only cash has significant influence to profitability. Keywords: earnings management, konvergensi IFRS, leverage, sales growth